2016
DOI: 10.1371/journal.pone.0165623
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Ghana’s National Health Insurance Scheme on Maternal and Infant Health Care Utilization

Abstract: Increasing equitable access to health care is a main challenge African policy makers are facing. The Ghanaian government implemented the National Health Insurance Scheme in 2004 and the aim of this study is to evaluate its early effects on maternal and infant healthcare use. We exploit data on births before and after the intervention and apply propensity score matching to limit the bias arising from self-selection into the health insurance. About forty percent of children had a mother who is enrolled in this i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
55
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(62 citation statements)
references
References 22 publications
6
55
0
1
Order By: Relevance
“…In 2007, this policy was formally integrated into the NHIS, which also expanded free ANC coverage from public health facilities only to all public and accredited private and faith-based health-care providers [28]. This was found to significantly increase the percentage of children whose mothers obtained at least four ANC visits [29].…”
Section: Discussionmentioning
confidence: 99%
“…In 2007, this policy was formally integrated into the NHIS, which also expanded free ANC coverage from public health facilities only to all public and accredited private and faith-based health-care providers [28]. This was found to significantly increase the percentage of children whose mothers obtained at least four ANC visits [29].…”
Section: Discussionmentioning
confidence: 99%
“…Also, individuals with insurance are more likely to be from high‐income groups, educated, and from urban areas. These selection factors complicate the comparison of the insured and uninsured women and could cause bias unless they are carefully controlled for (Gertler et al ., ; Bonfrer, Breebaart, & Van de Poel, ; Wang, Temsah, & Mallick, ). We conduct a propensity score matching (PSM) analysis to limit the bias due to confounding factors when estimating the treatment effect by comparing outcomes between the treatment (the insured) and the artificial control groups (the uninsured).…”
Section: Methodsmentioning
confidence: 99%
“…At the national level, family planning demand satisfied showed the least likelihood of reaching its target and the reason could be attributed to the fact that this service is not covered under NHIS but implemented through a government vertical program [19] and this pattern is consistent with a previous study [20]. The low uptake of family planning can be explained by many facets such as misconception, stigma, lack of knowledge, religious abhorrence, spousal disapproval, and inaccessibility [21].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a study done in rural Ghana found that enrollment into NHIS is 2.5 times more among the rich than the poor [29]. This deviates from NHIS’ original equity goal, which was to increase affordability and utilization of health services especially among the poor and vulnerable population [19]. If the poor are not insured, there is an increased likelihood of illnesses resulting in worse health status and further impoverishment.…”
Section: Discussionmentioning
confidence: 99%